Verfication of empirical formuals for calculating mean low flow in reflect to affecting on disposable water resources - Dariusz Piotr Młyński; Andrzej Wałęga; Piotr Bugajski; Agnieszka Operacz; Karolina Kurek (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The study evaluated verification of empirical formulas for calculating mean low flow (MLF) in reflect to shaping disposable water resources for mountain catchments, located in upper Vistula Basin. The following empirical formulas were analyzed: Punzet and Stachý.